2019
DOI: 10.1002/ajoc.201900509
|View full text |Cite
|
Sign up to set email alerts
|

Selective N‐Monomethylation of Anilines with Methanol Catalyzed by Commercial Pd/C as an Efficient and Reusable Catalyst

Abstract: N-methylation of amines is one of the most important CÀ N bond-forming reactions and is widely utilized for the synthesis of numerous agrochemicals, drugs, natural products, and dyes. In this paper, the N-monomethylation of aniline derivatives using Pd/C catalyst and methanol as the methylation reagent was investigated. The N-monomethylation of various anilines was achieved with high activity and selectivity under relatively mild reaction conditions, and the yield of N-monomethyl anilines was over 90 %. Notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Later, Watanabe and co‐workers [23] used RuCl 3 .nH 2 O/P(OBu) 3 catalytic system for N ‐methylation of amines with methanol at 180 °C, but the substrate scope is very narrow. After their seminal work, many groups have extended the state of selective N ‐methylation of amines or nitroarenes with methanol in presence of noble‐ [3a–e,h,l‐q,s,u‐z,aa, ac‐ae,24] and non‐noble metals ‐ [3f,g,i–k,r,t, ab, af‐ag] . Regarding ruthenium catalysis, to date only five homogeneous catalytic systems are reported ( Figure 1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Later, Watanabe and co‐workers [23] used RuCl 3 .nH 2 O/P(OBu) 3 catalytic system for N ‐methylation of amines with methanol at 180 °C, but the substrate scope is very narrow. After their seminal work, many groups have extended the state of selective N ‐methylation of amines or nitroarenes with methanol in presence of noble‐ [3a–e,h,l‐q,s,u‐z,aa, ac‐ae,24] and non‐noble metals ‐ [3f,g,i–k,r,t, ab, af‐ag] . Regarding ruthenium catalysis, to date only five homogeneous catalytic systems are reported ( Figure 1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, LC‐MS analysis indicated formation of a mono‐methylated diarylindigo whereas dimethylation was not observed (Figure S10). Pd‐catalyzed aniline N ‐methylation has been previously described [54] . Cross‐coupling at lower temperature (90 °C) in i PrOH under microwave irradiation in the presence of 5 equiv of arylboronic acid, 0.1 equiv Na 2 PdCl 4 , 0.25 equiv sSPhos, and 6 equiv K 3 PO 4 gave the unmethylated target compound, accompanied only by minor side products (Figure 3 A/B).…”
Section: Methodsmentioning
confidence: 90%
“…Pd-catalyzeda niline N-methylation has been previously described. [54] Cross-coupling at lower temperature (90 8C) in iPrOH under microwavei rradiation in the presence of 5equiv of arylboronic acid, 0.1 equiv Na 2 PdCl 4 , 0.25 equivs SPhos, and 6equiv K 3 PO 4 gave the unmethylated target compound, accompanied only by minor side products ( Figure 3A/B). Formation of the diarylindigo 6,6'-8 succeeded when using 4-hydroxyphenylboronic acid:T he target diarylindigo among other cross-coupling components and homocoupled product were detectable in the reaction solution as well as in the precipitate ( Figure 3B).…”
Section: #P Roductmentioning
confidence: 99%
“…When the reaction performed at a higher temperature (180 °C) the conversion of 1 a reached 88% in only 1 h, however the selectivity of N ‐monomethylation decreased, and the yield of 2 a was 51% (Table 1, entry 5). We have found that the commercially available Pd/C can serve as an efficient catalyst for the N ‐monomethylation of anilines with methanol [16a] . However, the Pd/C catalyst did not work well for the N‐ monomethylation of 1 a , and it only gave N ‐monomethylation product 2 a in yield of 58% with 68% selectivity in 8 h (Table 1, entry 6).…”
Section: Entry Cat Atmopshere Temperature [°C] Time [H] Conversion[b]...mentioning
confidence: 99%